Augustine's Confessions : a biography - Wills, Garry, 1934- (Princeton, N.J. : Princeton University Press, 2011)
"... Tells the story of theConfessions--what motivated Augustine to dictate it, how it asks to be read, and the many ways it has been misread in the one-and-a-half millennia since it was composed. Following Wills's biography of Augustine and his translation of theConfessions, this is an unparalleled introduction to one of the most important books in the Christian and Western traditions. Understandably fascinated by the story of Augustine's life, modern readers have largely succumbed to the temptation to read theConfessions as autobiography. But, Wills argues, this is a mistake. The book is not autobiography but rather a long prayer, suffused with the language of Scripture and addressed to God, not man. Augustine tells the story of his life not for its own significance but in order to discern how, as a drama of sin and salvation leading to God, it fits into sacred history. "We have to read Augustine as we do Dante, " Wills writes, "alert to rich layer upon layer of Scriptural and theological symbolism." Wills also addresses the long afterlife of the book, from controversy in its own time and relative neglect during the Middle Ages to a renewed prominence beginning in the fourteenth century and persisting to today, when theConfessionshas become an object of interest not just for Christians but also historians, philosophers, psychiatrists, and literary critics"--Jacket.
The book's birth -- The book's genre -- The book's African days -- The book's Ambrose -- The book's "conversion" -- The book's baptismal days -- The book's hinge -- The book's culmination -- The book's afterlife : early reception, later neglect.
Includes bibliographical references (p. 155) and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430.